Content Validity to Assess the LMS-Moodle-based Academic Writing Learning Model of Arabic - Ari Khairurrijal Fahmi; Miatin Rachmawati; Kamal Surong (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
The aim of study was a deep understanding of the description of content validity of a LMS-Moodle Based to support learning Arabic academic writing. This research focused on tracing LMS that are suitable to be used to carry out Arabic academic writing learning in college. This study used a Research and Development method that combines two research methods to describe the validation mechanism of the LMS-Moodle Based device for learning of Arabic writing. To develop this research instrument, the researchers developed an instrument based on the IPA Matrix analysis. After developing the instrument, LMS assessment was carried out by several experts in the field of learning media who assessed the LMS used in learning Arabic academic writing. The results of this study indicated that the LMS used for learning Arabic academic writing is feasible to use based on the measurement of the matrix science.